Pengaruh Pergantian Manajemen dan Audit Fee pada Auditor Switching dengan Reputasi Auditor Sebagai Variabel Pemoderasi - Wulandari, Made Widi; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
Auditor turnover is a behavior that the client company does to transfer the auditor. The purpose of this research is to know and prove empirically the effect of management change and audit fee on switching auditor with auditor reputation as moderator variable. This research was conducted at manufacturing sector companies listed in Indonesia Stock Exchange (BEI) year 2012-2016. The population in this study amounted to 144 companies, by using purposive sampling technique obtained by a sample of 18 companies. Data analysis techniques used are descriptive statistical analysis, logistic regression analysis and interaction test. The test results show that the change of management has a positive influence on the switching auditor, then audit fee has no effect on the switching auditor and the auditor's reputation can not moderate the effect of switching management on the switching auditor. Keywords: auditors switching, change of management, audit fees.